Electronics : a course book for students - Olsen, G. H. (Butterworth, 1982)
Electronics: A Course Book for Students, Second Edition, provides a general introduction to electronics for those who find formal or examination texts to be unsuitable for their needs. This revised text includes more analytical work on circuits. Examples and examination-type exercises are also provided. The book's early chapters focus on the basic components, such as resistors, capacitors, inductors, and transistors. Readers are then introduced to combinations of these components that form the fundamental circuits from which most electronic equipment is built. Semiconductor devices are also di.